"Why do you make me hate myself?": Re-teaching Whiteness, abuse, and love in urban teacher education. Issue 2 (2nd April 2016) - Matias, Cheryl E.
Abstract : Teacher educators are constantly trying to improve the field to meet the needs of a growing urban populace. Inclusion of socially just philosophies in the curriculum is indeed essential, yet it can mask the recycling of normalized, oppressive Whiteness. This reflective and theoretical paper employs critical race theory and critical Whiteness studies to deconstruct Whiteness, abuse, and love in teacher education. Using an interdisciplinary and emotion-based approach to understanding Whiteness, this paper examines how denying race during white childhood via a color-blind ideology leaves lasting emotional scars, impressions that perpetuate the institutional silencing of race in teacher education. This "abuse" is projected onto urban students of color and, more broadly, people of color. This paper asserts that until teacher education programs make confronting and exploring Whiteness a priority, they cannot truly love their urban students of color as complete beings and so deny humanity full and just consideration.